Efficacy and safety of the CRTh2 antagonist AZD1981 as add-on therapy to inhaled corticosteroids and long-acting β2-agonists in patients with atopic asthma - Bateman ED; O'Brien C; Rugman P; Luke S; Ivanov S; Uddin M (Dove Medical Press, 2018)
Eric D Bateman,1 Christopher O’Brien,2 Paul Rugman,2 Sally Luke,2 Stefan Ivanov,2 Mohib Uddin2,3 1Department of Medicine, University of Cape Town, Cape Town, 7700, South Africa; 2Research and Development, 3Respiratory, Inflammation, and Autoimmunity, IMED Biotech Unit, AstraZeneca, Gothenburg, SE-431 83, Sweden Objectives: To evaluate the efficacy and safety of AZD1981, a potent, specific antagonist of the CRTh2 receptor, as add-on therapy to inhaled corticosteroids (ICS) and long-acting β2-agonists (LABA), in patients with persistent asthma with an allergic component.Patients and methods: In this placebo-controlled, parallel-group Phase IIb study, patients with persistent atopic asthma on ICS and LABA were randomized to receive 12 weeks of treatment with placebo or AZD1981 (80 mg daily, 200 mg daily, and 10 mg, 40 mg, 100 mg, or 400 mg twice daily [BID]). The primary end point was the mean change from baseline in predose, prebronchodilator forced expiratory volume in 1 second (FEV1) averaged over weeks 2, 4, 8, and 12 in the AZD1981-treatment group vs the placebo group. Secondary end points included other measures of lung function, symptoms, and asthma control, as well as standard measures of safety.Results: In total, 1,140 patients (99.7%) received study treatment. There were improvements in the primary end point across all treatment groups over 12 weeks of treatment. However, the improvement for the highest AZD1981 dose (400 mg BID) vs placebo was not statistically significant (0.02 L, P=0.58), preventing interpretation of statistical testing for the lower doses. AZD1981 was well tolerated, and the incidence of adverse events was comparable across placebo and treatment groups.Conclusion: In patients with allergic asthma receiving ICS and LABA therapy, the addition of AZD1981 at doses up to 400 mg BID failed to produce a clinically relevant improvement in lung function or any other measured end point, but appeared to have an acceptable safety profile. This clinical study is registered with ClinicalTrials.gov (NCT01197794). Keywords: allergic asthma, AZD1981, CRTh2 antagonist, efficacy, safety, eosinophils